Radiation-induced cardiac side-effects: The lung as target for interacting damage and intervention - Wiedemann, Julia; Coppes, Robert P.; van Luijk, Peter (Frontiers in Oncology, 2022)
For many thoracic cancers, radiotherapy is part of its treatment. Often heart and lung tissue receive significant doses of radiation. Dose to the heart can potentially lead to cardiac effects like pericarditis and myocardial fibrosis. Common side effects after lung irradiation are pneumonitis and pulmonary fibrosis. However, it has been shown that lung irradiation also has effects on cardiac function. In a rat model lung irradiation caused remodeling of the pulmonary vasculature increasing resistance of the pulmonary vascular bed, leading to enhanced pulmonary artery pressure, right ventricle hypertrophy and reduced right ventricle performance. Even more pronounced effects are observed when both, lung and heart are irradiated. The effects observed after lung irradiation show striking similarities with symptoms of pulmonary arterial hypertension. Especially, the vascular remodeling in lung tissue seems to have similar underlying features. Here, we want to discuss similarities and differences of vascular remodeling observed after thoracic irradiation compared to those in pulmonary arterial hypertension patients and research models. Finally, we will assess how this knowledge about similarities in the mechanisms of vascular remodeling in pulmonary hypertension and after irradiation could potentially be translated into interventions that would be beneficial for patients treated for thoracic tumors, where dose to lung tissue can often not be avoided.